+0

# Create an equation that has the three solutions x=2,4, and 5.

0
37
1

Create an equation that has the three solutions x=2,4, and 5.

Guest Aug 12, 2017

#1
+1802
+3

To find an equation that has the three solutions of 2, 4, and 5, first set each solution equal to x.

$$x=2$$

$$x=4$$

$$x=5$$

Next, figure out what number goes with each of the three solutions that makes x equal to zero on the right side.  For x=2, the number will be -2; for x=4, the number is -4; for x=5, the number will be -5. What you do on the right side, you do to the left side as well.

$$x=2$$

$$x-2=2-2$$

$$x-2=0$$

$$x=4$$

$$x-4=4-4$$

$$x-4=0$$

$$x=5$$

$$x-5=5-5$$

$$x-5=0$$

Next, combine all three equations using the zero product.

$$(x-2)\times(x-4)\times(x-5)=0$$

Next, expand the left side.

$$(x-2)\times(x-4)\times(x-5)=0$$

$$({x}^{2}-4x-2x+8)\times(x-5)=0$$

$$({x}^{2}-6x+8)\times(x-5)=0$$

$${x}^{3}-5{x}^{2}-6{x}^{2}+30x+8x-40=0$$

$${x}^{3}-11{x}^{2}+38x-40=0$$

Next, replace 0 on the right side with y and then switch the equation around so that the y is on the left side.

$${x}^{3}-11{x}^{2}+38x-40=y$$

$$y={x}^{3}-11{x}^{2}+38x-40$$

gibsonj338  Aug 12, 2017
edited by gibsonj338  Aug 12, 2017
Sort:

#1
+1802
+3

To find an equation that has the three solutions of 2, 4, and 5, first set each solution equal to x.

$$x=2$$

$$x=4$$

$$x=5$$

Next, figure out what number goes with each of the three solutions that makes x equal to zero on the right side.  For x=2, the number will be -2; for x=4, the number is -4; for x=5, the number will be -5. What you do on the right side, you do to the left side as well.

$$x=2$$

$$x-2=2-2$$

$$x-2=0$$

$$x=4$$

$$x-4=4-4$$

$$x-4=0$$

$$x=5$$

$$x-5=5-5$$

$$x-5=0$$

Next, combine all three equations using the zero product.

$$(x-2)\times(x-4)\times(x-5)=0$$

Next, expand the left side.

$$(x-2)\times(x-4)\times(x-5)=0$$

$$({x}^{2}-4x-2x+8)\times(x-5)=0$$

$$({x}^{2}-6x+8)\times(x-5)=0$$

$${x}^{3}-5{x}^{2}-6{x}^{2}+30x+8x-40=0$$

$${x}^{3}-11{x}^{2}+38x-40=0$$

Next, replace 0 on the right side with y and then switch the equation around so that the y is on the left side.

$${x}^{3}-11{x}^{2}+38x-40=y$$

$$y={x}^{3}-11{x}^{2}+38x-40$$

gibsonj338  Aug 12, 2017
edited by gibsonj338  Aug 12, 2017

### 10 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details